2012
DOI: 10.1016/j.ecolmodel.2011.12.022
|View full text |Cite
|
Sign up to set email alerts
|

A flood pulse driven fish population model for the Okavango Delta, Botswana

Abstract: openAccessArticle: FalsePage Range: 27-27doi: 10.1016/j.ecolmodel.2011.12.022Harvest Date: 2016-01-12 15:11:21issueName:cover date: 2012-03-10pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 99 publications
(108 reference statements)
0
18
0
Order By: Relevance
“…This GSA/UA of the ORI reservoir model presents a novel demonstration of a previously described generic method for objectively reducing and refining uncertainty (Linhoss et al, 2012) which is especially relevant for data-scarce areas. It also provides important insights into the hydrology of the Okavango Delta, the sensitivity and uncertainty of the ORI model, and reservoir models in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This GSA/UA of the ORI reservoir model presents a novel demonstration of a previously described generic method for objectively reducing and refining uncertainty (Linhoss et al, 2012) which is especially relevant for data-scarce areas. It also provides important insights into the hydrology of the Okavango Delta, the sensitivity and uncertainty of the ORI model, and reservoir models in general.…”
Section: Discussionmentioning
confidence: 99%
“…MCF has been shown to reduce the variance in model outputs and to be useful in calibration (Rose et al, 1991). Here, we use MCF to redefine prior PDFs based on the goodness of the model fit (Linhoss et al, 2012). Redefining prior PDF's based on the MCF results represents a novel method for reducing model uncertainty in a reservoir model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Mosepele et al [81] also observed habitat partitioning in fish species assemblages of the delta, where upper delta habitats have relatively higher species diversity than lower delta habitats [79]. Several studies have shown that the flood pulse is a key driver in the delta's fish community [75,80,[84][85][86]. Similar fish species from different habitats in the Delta have different life history strategies [82,87], which is driven primarily by differences in environmental conditions [85].…”
Section: Biology and Ecology Of Fisheriesmentioning
confidence: 99%
“…Ephemeral wetland systems at the terminus of dryland river systems are subject to spectacular pulses of biological productivity (Roshier, Robertson, & Kingsford, 2002). The pulsing of high in-stream flows, or "freshes," is an important trigger for the breeding of fish (Humphries, King, & Koehn, 1999;Linhoss, Muñoz-Carpena, Allen, Kiker, & Mosepele, 2012). The flooding of river benches and floodplains mobilises carbon remineralised during the dry phase (Kobayashi et al, 2009;Woodward, Fellows, Mitrovic, & Sheldon, 2015), while overbank inundation of floodplains leads to the resprouting of senescent reedbeds and the germination of herbaceous plants from seed (Froend & Mccomb, 1994).…”
Section: Introductionmentioning
confidence: 99%